2017
DOI: 10.3892/ol.2017.6244
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FOXC2, PinX1, Ki-67 and Cyclin D1 in cutaneous cell carcinoma

Abstract: We investigated the expression of FOXC2, PinX1, Ki-67 and Cyclin D1 in cutaneous cell carcinoma. We collected 30 cutaneous squamous cell carcinoma (SCC), 30 cutaneous basal cell carcinoma (BCC) and 30 normal skin tissues. The protein expression and gene expression of FOXC2, endogenous telomerase-inhibiting gene PinX1, Ki-67 and Cyclin D1 was measured by immunohistochemistry (IHC) and semi-quantitative reverse transcription polymerase chain reaction (RT-PCR), respectively. In SCC and BCC tissues, the positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In addition, semi-quantitative RT-PCR was performed as previously described [ 17 ], using the following primers: FOXC2-2F CGCCCGAGAAGAAGATCAC; FOXC2-2R CGCTCTTGATCACCACCTTC; FOXC2-AS1-2F CTTGCCGGGCTTCTTGTCGT; FOXC2-AS1-2R TACATTTTCGTCTTCTGTTCTTTTATTGG. To exclude DNA contamination, FOXC2 expression analysis was carried out on samples with and without reverse transcriptase (+RT and −RT).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, semi-quantitative RT-PCR was performed as previously described [ 17 ], using the following primers: FOXC2-2F CGCCCGAGAAGAAGATCAC; FOXC2-2R CGCTCTTGATCACCACCTTC; FOXC2-AS1-2F CTTGCCGGGCTTCTTGTCGT; FOXC2-AS1-2R TACATTTTCGTCTTCTGTTCTTTTATTGG. To exclude DNA contamination, FOXC2 expression analysis was carried out on samples with and without reverse transcriptase (+RT and −RT).…”
Section: Methodsmentioning
confidence: 99%
“…Staining score was defined as follows: score 0, ≤5%; score 1, 6–25%; score 2, 26–50%; score 3, 51–75% and score 4, >76% of cells were stained. The final immunoreactivity score was calculated as the sum of the grade and staining scores ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…A number of investigations reported a considerable and at times significant decrease in the ki67 labeling index of BCC compared to SCC. 15 , 16 On the other hand, Abdou et al demonstrated an increased expression of MCM2 in BCC when compared to SCC. 17 …”
Section: Introductionmentioning
confidence: 99%